2019
DOI: 10.3390/jimaging5010010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Leaf Primordia of Potato Tubers Using Sensor Fusion and Wavelength Selection

Abstract: The sprouting of potato tubers during storage is a significant problem that suppresses obtaining high quality seeds or fried products. In this study, the potential of fusing data obtained from visible (VIS)/near-infrared (NIR) spectroscopic and hyperspectral imaging systems was investigated, to improve the prediction of primordial leaf count as a significant sign for tubers sprouting. Electronic and lab measurements were conducted on whole tubers of Frito Lay 1879 (FL1879) and Russet Norkotah (R.Norkotah) pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…i.e., high at 900 nm, decreased to 1400 nm, and then increased to 1700 nm. The water content in the samples caused significant absorbance peaks at 995 nm, 1210 nm, and 1435 nm [12]. The absorbance of Noninfected (N) potatoes was higher than that of infected (I) potatoes at 990 nm and 1210 nm, which could be attributed to their higher water content.…”
Section: B Visible and Near-infrared (Vis/nir) Spectramentioning
confidence: 94%
See 1 more Smart Citation
“…i.e., high at 900 nm, decreased to 1400 nm, and then increased to 1700 nm. The water content in the samples caused significant absorbance peaks at 995 nm, 1210 nm, and 1435 nm [12]. The absorbance of Noninfected (N) potatoes was higher than that of infected (I) potatoes at 990 nm and 1210 nm, which could be attributed to their higher water content.…”
Section: B Visible and Near-infrared (Vis/nir) Spectramentioning
confidence: 94%
“…Several noninvasive methodologies, such as spectroscopic techniques, computer vision systems, and ultrasound methods, have been extensively examined to evaluate internal defects in potato tubers. However, the efficacy of these techniques varies depending on the specific type of defect [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In Radi et al [ 1 ], data spectral fusion is shown as coming from a Visible and Near Infrared VIS/NIR spectroscopic system and from a VIS/NIR hyperspectral imaging systems used respectively in interactance mode and in reflection mode with the aim of acquiring the spectral information of whole tubers for predicting the primordial leaf count of potatoes. In particular, the HSI unit uses an optical fiber to illuminate a large portion of the sampled potato with the imaging spectrograph directly attached to a CCD camera, acquiring spectral information along a line of the potato that is held by a scanner system, therefore in push broom modality.…”
Section: Contributionsmentioning
confidence: 99%